RS Aggrawal 2020 2021 Solutions for Class 6 Maths Chapter 6 Simplification are provided here with simple step-by-step explanations. These solutions for Simplification are extremely popular among class 6 students for Maths Simplification Solutions come handy for quickly completing your homework and preparing for exams. All questions and answers from the RS Aggrawal 2020 2021 Book of class 6 Maths Chapter 6 are provided here for you for free. You will also love the ad-free experience on Meritnation’s RS Aggrawal 2020 2021 Solutions. All RS Aggrawal 2020 2021 Solutions for class 6 Maths are prepared by experts and are 100% accurate.

#### Question 1:

Given expression:
= 21 - 12 $÷$ 3 â¨¯ 2
= 21 - 4 â€‹â¨¯ 2               [Performing division]
= 21 -  8                     [Performing multiplication]
= 13                           [Performing subtraction]

#### Question 2:

Given expression:
= 21 - 12 $÷$ 3 â¨¯ 2
= 21 - 4 â€‹â¨¯ 2               [Performing division]
= 21 -  8                     [Performing multiplication]
= 13                           [Performing subtraction]

Given expression:
= 16 + 8 $÷$ 4 - 2 â¨¯ 3
= 16 + 2 - 2 â€‹â¨¯ 3               [Performing division]
= 16 + 2 - 6                     [Performing multiplication]
= 18 - 6                           [Performing addition]
= 12                               â€‹ [Performing subtraction]

#### Question 3:

Given expression:
= 16 + 8 $÷$ 4 - 2 â¨¯ 3
= 16 + 2 - 2 â€‹â¨¯ 3               [Performing division]
= 16 + 2 - 6                     [Performing multiplication]
= 18 - 6                           [Performing addition]
= 12                               â€‹ [Performing subtraction]

Given expression:
= 13 - (12 - 6 ÷ 3 )
= 13 - (12 - 2)       [Performing division]
= 13 - 10 = 3
[Performing subtraction]

#### Question 4:

Given expression:
= 13 - (12 - 6 ÷ 3 )
= 13 - (12 - 2)       [Performing division]
= 13 - 10 = 3
[Performing subtraction]

Given expression:
= 19 - [4 + {16 - (12 - 2)}]
19 - [4 + {16 - 10}]                        [Removing parentheses]
= 19 - [4 + 6]                                    [Removing braces]
= 19 - 10                                           [Removing square brackets]
= 9

#### Question 5:

Given expression:
= 19 - [4 + {16 - (12 - 2)}]
19 - [4 + {16 - 10}]                        [Removing parentheses]
= 19 - [4 + 6]                                    [Removing braces]
= 19 - 10                                           [Removing square brackets]
= 9

Given expression:
= 36 - [18 - {14 - (15 - 4 ÷ 2 × 2)}]
36 - [18 - {14 - (15 - 2 × 2)}]                   [Performing division]
36 - [18 - {14 - (15 - 4)}]                         [Performing multiplication]
=
36 - [18 - {14 - 11}]                                [Removing parentheses]
=
36 - [18 - 3]                                            [Removing braces]
â€‹= 36 - 15                                                   [Removing square brackets]
= 21

#### Question 6:

Given expression:
= 36 - [18 - {14 - (15 - 4 ÷ 2 × 2)}]
36 - [18 - {14 - (15 - 2 × 2)}]                   [Performing division]
36 - [18 - {14 - (15 - 4)}]                         [Performing multiplication]
=
36 - [18 - {14 - 11}]                                [Removing parentheses]
=
36 - [18 - 3]                                            [Removing braces]
â€‹= 36 - 15                                                   [Removing square brackets]
= 21

Given expression:
= 27 - [18 - {16 - (5 - $\overline{)4-1}$)}]
=
27 - [18 - {16 - (5 - 3)}]                       [Removing bar]
=
27 - [18 - {16 - 2}]                              [Removing parentheses]
27 - [18 - 14]                                       [Removing braces]
= 2
7 - 4                                                 [Removing square brackets]
â€‹= 23

#### Question 7:

Given expression:
= 27 - [18 - {16 - (5 - $\overline{)4-1}$)}]
=
27 - [18 - {16 - (5 - 3)}]                       [Removing bar]
=
27 - [18 - {16 - 2}]                              [Removing parentheses]
27 - [18 - 14]                                       [Removing braces]
= 2
7 - 4                                                 [Removing square brackets]
â€‹= 23

Given expression:

#### Question 8:

Given expression:

Given expression:

#### Question 9:

Given expression:

The given expression

#### Question 10:

The given expression

Given expression:

#### Question 11:

Given expression:

Given expression:

#### Question 12:

Given expression:

Given expression:

#### Question 13:

Given expression:

Given expression:

#### Question 14:

Given expression:

Given expression:

#### Question 15:

Given expression:

Given expression:

#### Question 1:

Given expression:

(c ) 18

Explanation:
= 8 + 4 ÷ 2 × 5
= 8 + 2 × 5
= 8 + 10 = 18

#### Question 2:

(c ) 18

Explanation:
= 8 + 4 ÷ 2 × 5
= 8 + 2 × 5
= 8 + 10 = 18

( b ) 12

Explanation:
= 54 ÷ 3 of 6 + 9
= 54 ÷ (3  x 6) + 9
= 54 ÷ 18 + 9
= 3 + 9 = 12

#### Question 3:

( b ) 12

Explanation:
= 54 ÷ 3 of 6 + 9
= 54 ÷ (3  x 6) + 9
= 54 ÷ 18 + 9
= 3 + 9 = 12

(b ) 3

Explanation:
= 13 - (12 - 6 ÷ 3)
= 13 - (12 - 2)
= 13 - 10 = 3

#### Question 4:

(b ) 3

Explanation:
= 13 - (12 - 6 ÷ 3)
= 13 - (12 - 2)
= 13 - 10 = 3

(a ) 7

Explanation:
= 1001 ÷  11 of 13
= 1001 ÷ ( 11 x 13)
= 1001 ÷ 143 = 7

#### Question 5:

(a ) 7

Explanation:
= 1001 ÷  11 of 13
= 1001 ÷ ( 11 x 13)
= 1001 ÷ 143 = 7

(b) 121

Explanation:
Given expression:
= 133 + 28 $÷$ 7 - 8 â¨¯ 2
= 133 + 4 - 8 â€‹â¨¯2              [Performing division]
= 133 + 4 - 16                 [Performing multiplication]
= 137 - 16                       [Performing addition]
= 121                              [Performing subtraction]

#### Question 6:

(b) 121

Explanation:
Given expression:
= 133 + 28 $÷$ 7 - 8 â¨¯ 2
= 133 + 4 - 8 â€‹â¨¯2              [Performing division]
= 133 + 4 - 16                 [Performing multiplication]
= 137 - 16                       [Performing addition]
= 121                              [Performing subtraction]

(a) 3636

Explanation:
Given expression:
= 3640 - 14 $÷$ 7 â¨¯ 2
â€‹= 3640 - 2  â€‹â¨¯2               [Performing division]
= 3640 - 4                    [Performing multiplication]
= 3636                          [Performing subtraction]

#### Question 7:

(a) 3636

Explanation:
Given expression:
= 3640 - 14 $÷$ 7 â¨¯ 2
â€‹= 3640 - 2  â€‹â¨¯2               [Performing division]
= 3640 - 4                    [Performing multiplication]
= 3636                          [Performing subtraction]

(b) 920

Explanation:
Given expression:
= 100 â¨¯ 10 $-$ 100 + 2000 $÷$ 100
â€‹= 100 â¨¯ 10 $-$ 100 + 20                  [Performing division]
= 1000 $-$ 100 + 20                        [Performing multiplication]
= 1020 $-$100                                 [Performing addition]
= 920                                   â€‹        [Performing subtraction]

#### Question 8:

(b) 920

Explanation:
Given expression:
= 100 â¨¯ 10 $-$ 100 + 2000 $÷$ 100
â€‹= 100 â¨¯ 10 $-$ 100 + 20                  [Performing division]
= 1000 $-$ 100 + 20                        [Performing multiplication]
= 1020 $-$100                                 [Performing addition]
= 920                                   â€‹        [Performing subtraction]

(b) 23
Explanation:

Given expression:
= 27 $-$ [18 $-$ {16 $-$ (5 $-$ $\overline{)4-1}$)}]
=  27 $-$ [18 $-$ {16 $-$ (5 $-$ 3)}]                          (Removing bar)
= 27 $-$ [18 $-$ {16 $-$ 2}]                                   (Removing parentheses)
= 27 $-$ [18 $-$ 14]                                            (Removing braces)
= 27 $-$ 4                                                        (Removing square brackets)
= 23

#### Question 9:

(b) 23
Explanation:

Given expression:
= 27 $-$ [18 $-$ {16 $-$ (5 $-$ $\overline{)4-1}$)}]
=  27 $-$ [18 $-$ {16 $-$ (5 $-$ 3)}]                          (Removing bar)
= 27 $-$ [18 $-$ {16 $-$ 2}]                                   (Removing parentheses)
= 27 $-$ [18 $-$ 14]                                            (Removing braces)
= 27 $-$ 4                                                        (Removing square brackets)
= 23

(a) 29
Explanation:
Given expression:
= 32 $-$ [48 $÷$ {36 $-$ ( 27 $-$ $\overline{)16-9}$)}]
=  32 $-$ [48 $÷$ {36 $-$ ( 27 $-$ 7)}]                    (Removing bar)
= 32 $-$ [48 $÷$ {36 $-$20}]                               (Removing parentheses)
= 32 $-$ [48 $÷$ 16]                                          (Removing braces)
= 32 $-$ 3                                                      (Removing square brackets)
= 29

#### Question 10:

(a) 29
Explanation:
Given expression:
= 32 $-$ [48 $÷$ {36 $-$ ( 27 $-$ $\overline{)16-9}$)}]
=  32 $-$ [48 $÷$ {36 $-$ ( 27 $-$ 7)}]                    (Removing bar)
= 32 $-$ [48 $÷$ {36 $-$20}]                               (Removing parentheses)
= 32 $-$ [48 $÷$ 16]                                          (Removing braces)
= 32 $-$ 3                                                      (Removing square brackets)
= 29

(a ) 6

Explanation:
Given expression:
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 18 ÷ 9 × 8)}]                        [Performing division]
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 2 ×  8)}]                               [Performing multiplication]
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 16)}]
= 8 $-$ [28 ÷ {34 $-$ 20}]                                              [Removing parentheses]
= 8 $-$ [28 ÷ 14]                                                         [Removing braces]
= 8 $-$ 2 = 6                                                               [Removing square brackets]

#### Question 1:

(a ) 6

Explanation:
Given expression:
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 18 ÷ 9 × 8)}]                        [Performing division]
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 2 ×  8)}]                               [Performing multiplication]
= 8 $-$ [28 ÷ {34 $-$ (36 $-$ 16)}]
= 8 $-$ [28 ÷ {34 $-$ 20}]                                              [Removing parentheses]
= 8 $-$ [28 ÷ 14]                                                         [Removing braces]
= 8 $-$ 2 = 6                                                               [Removing square brackets]

We have:
16 - [11 + {8 - (6 -$\overline{)4-2}$ )}]
= â€‹16 - [11 + {8 - (6 - 2)}]         (Removing bar)
= â€‹16 - [11 + {8 - 4}]
= â€‹16 - [11 + 4]                           (Removing barces)
= 16 - 15                                          (Removing square brackets)
= 1

#### Question 2:

We have:
16 - [11 + {8 - (6 -$\overline{)4-2}$ )}]
= â€‹16 - [11 + {8 - (6 - 2)}]         (Removing bar)
= â€‹16 - [11 + {8 - 4}]
= â€‹16 - [11 + 4]                           (Removing barces)
= 16 - 15                                          (Removing square brackets)
= 1

We have:
16 + 8 $÷$ 4 $-$ 2 $×$ 3
16 + 2 $-$ 2 $×$ 3             (Division)
16 + 2 $-$ 6                   (Multiplication)
= 18 $-$ 6                           (Addition)
= 12

#### Question 3:

We have:
16 + 8 $÷$ 4 $-$ 2 $×$ 3
16 + 2 $-$ 2 $×$ 3             (Division)
16 + 2 $-$ 6                   (Multiplication)
= 18 $-$ 6                           (Addition)
= 12

Given expression:
36 - [18 - {14 - (15 - 4 ÷ 2 × 2)}]                                     [Performing division]
= 36 - [18 - {14 - (15 - 2 × 2)}]                                           [Performing multiplication]
= 36 - [18 - {14 - (15 - 4)}]
= 36 - [18 - {14 - 11}]                                                        [Removing parentheses]
= 36 - [18 - 3]                                                                    [Removing braces]
= 36 - 15                                                                           [Removing square brackets]
= 21

#### Question 4:

Given expression:
36 - [18 - {14 - (15 - 4 ÷ 2 × 2)}]                                     [Performing division]
= 36 - [18 - {14 - (15 - 2 × 2)}]                                           [Performing multiplication]
= 36 - [18 - {14 - (15 - 4)}]
= 36 - [18 - {14 - 11}]                                                        [Removing parentheses]
= 36 - [18 - 3]                                                                    [Removing braces]
= 36 - 15                                                                           [Removing square brackets]
= 21

(c) 17
We have:
15 + 5 ÷ 5 x 2
= 15 +1 x 2              (Performing division)
= 15 + 2                  (Performing multiplication)
= 17

#### Question 5:

(c) 17
We have:
15 + 5 ÷ 5 x 2
= 15 +1 x 2              (Performing division)
= 15 + 2                  (Performing multiplication)
= 17

(c) $27\frac{5}{7}$
We have:
16 - 2 ÷ 7 +  6 × 2
= 16 - $\left(\frac{2}{7}\right)$ + 6 × 2                                                                [Performing division]
= 16 - $\left(\frac{2}{7}\right)$ + 12                                                                    [Performing multiplication]
= 28 - $\left(\frac{2}{7}\right)$                                                                            [Performing addition]
=                                     [Performing subtraction]

#### Question 6:

(c) $27\frac{5}{7}$
We have:
16 - 2 ÷ 7 +  6 × 2
= 16 - $\left(\frac{2}{7}\right)$ + 6 × 2                                                                [Performing division]
= 16 - $\left(\frac{2}{7}\right)$ + 12                                                                    [Performing multiplication]
= 28 - $\left(\frac{2}{7}\right)$                                                                            [Performing addition]
=                                     [Performing subtraction]